Road transport infrastructure and supply chain asset management: evidence from manufacturing firms in the Sub-Saharan African market - James Peprah Adu; Nirmala Dorasamy; Solomon Abekah Keelson (Cogent Social Sciences, 2024)
Transport is critical to the smooth operation of economic operations as well as to guarantee social well-being and demographic cohesion. Transport facilitates people’s daily mobility and is critical to the production and distribution of goods as well as companies. Nonetheless, existing studies have not adequately and empirically explored the relationship between road transport infrastructure and supply chain asset management within Sub-Sahara Africa. It is against this background that the current study seeks to investigate the relationship between road transport infrastructure and supply chain asset management from the perspective of a developing country using the manufacturing sector. Leveraging the resource-based-view theory, the study employs the SPSS and Partial Least Square Structural Equation Modeling (PLS-SEM) approach to explore this relationship and also for data processing and analysis. Based on a purposely selected sample of 359 senior managers of manufacturing firms in Ghana, the study found that two of the three proposed hypotheses were significant while one was insignificant. This study contributes to the growing literature on the affordances of supply chain asset management and road transport infrastructure in emerging economies. The study implications highlighted are beneficial to both industry players and researchers.